Effects of Oral Carotenoids on Oxidative Stress: A Systematic Review and Meta-Analysis of Studies in the Recent 20 Years - Zhuang, Chengfei; Yuan, Jinping; Du, Yimei; Zeng, Jing; Sun, Yan; Wu, Yan; Gao, Xing-Hua; Chen, Hong-Duo (Frontiers in Nutrition, 2022)
Carotenoids protect organs, tissues, and cells from the damaging action of singlet oxygen, oxygen radicals, and lipid peroxides. This systematic review was sought to evaluate the influence of oral carotenoids on antioxidant/oxidative markers, blood carotenoids levels, and lipid/lipoprotein parameters in human subjects. A comprehensive review of relevant literature was conducted in PubMed, Web of Sciences, and the Cochrane library, from 2000 to December 2020. Randomized controlled trials, case-controlled trials, or controlled trials were identified. A total of eighteen trials were included, with the target populations being healthy subjects in 16 studies, athletes in 1 study, and pregnant women in 1 study. The meta-analysis results showed that carotenoids complex supplementation significantly increased the levels of antioxidative parameters ferric-reducing ability of plasma (FRAP) and oxygen radical absorbance capacity (ORAC) [standardized mean difference (SMD) = 0.468; 95% CI: 0.159–0.776, p = 0.003; SMD = 0.568; 95% CI: 0.190–0.947, p = 0.003] and decreased the blood triglyceride (TG) level (SMD = −0.410, 95% CI: −0.698 to −0.122, p = 0.005). Oral carotenoids supplement significantly increased the blood levels of β-carotene (SMD = 0.490, 95% CI: 0.123–0.858, p = 0.009), α-tocopherol (SMD = 0.752, 95%CI: 0.020–1.485, p = 0.044), and the intaking durations were 8 weeks. The levels of antioxidative enzymes and other lipid/lipoprotein parameters were not different between subjects receiving carotenoids and controls (p > 0.05). In conclusion, our systematic review showed that the carotenoids complex is beneficial for alleviating potential oxidative stress via interacting with free radicals or decreasing blood TG levels. The intaking duration of carotenoids should be 8 weeks to reach enough concentration for function.